Effect of planting methods and humic acid application on productivity of soybean (Glycine max L.): EFFECT OF PLANTING METHODS AND HUMIC ACID APPLICATION ON PRODUCTIVITY OF SOYBEAN - SUMERPAL SINGH,; KANWALJIT SINGH SANDHU,; BHART, (Journal of Oilseeds Research, 2024)
An experiment was carried out during rainy season of 2022 and 2023 with 8 treatment combinations in randomised block design with three replications. Treatment T2 (Bed planting method with 15 kg HA + 100% RDF) gave significantly higher plant population (7.0), effective plant population (6.4), plant height (124 cm) at 120 DAS, number of branches/plant (8.6) at 120 DAS, dry matter accumulation (21.2 g/plant) at harvest, number of pods/plant (72.3), seed yield (1969 kg/ha), straw yield (2851 kg/ha), oil yield (374.2 kg/ha), protein yield (753.3 kg/ha) as compared to flat planting. Further results indicated that Treatment T2 (100% RDF + 15 kg/ha humic acid application on BP) proved beneficial for higher net returns (`49,739) and BC ratio (1.2).